Cul4B promotes the progression of ovarian cancer by upregulating the expression of CDK2 and CyclinD1 - Peng-jing Duan; Juan-hong Zhao; Li-li Xie (BMC, 2020)
Abstract Background Ovarian cancer is one of the most common malignant tumors in the female reproductive system with the highest mortality rate. Cul4B participates in the oncogenesis and progression of several malignant tumors. However, the role of Cul4B in ovarian cancer has not been studied. Results High expression of intratumor Cul4B was associated with poor patient survival. Cul4B expression was associated with FIGO stage and Cul4B was independent risk factor of ovarian cancer disease-free survival and overall survival. In vitro studies revealed that overexpression of Cul4B promoted tumor proliferation while knockdown of Cul4B significantly inhibited the proliferation capacity of ovarian cancer cells. Mechanistically, Cul4B was found to promotes cell entering S phase from G0/G1 phase by regulating the expression of CDK2 and CyclinD1. Cul4B regulates the expression of CDK2 and CyclinD1 by repressing miR-372. Conclusions The results revealed that high expression of Cul4B is associated with poor ovarian cancer prognosis and Cul4B may serve as a potential treating target for an adjuvant therapy.